2018
DOI: 10.1002/pbc.27352
|View full text |Cite
|
Sign up to set email alerts
|

Children with HbSβ0 thalassemia have higher hemoglobin levels and lower incidence rate of acute chest syndrome compared to children with HbSS

Abstract: We have provided preliminary evidence that clinically relevant differences occur in ACS rates and TCD velocities between children with HbSβ thalassemia and HbSS. Future SCD RCTs should consider balanced allocation of these SCD genotypes, particularly when ACS and abnormal TCD velocities are primary outcome measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…These findings are largely consistent with a prior study of HbSβ 0 (n = 22) and HbSS (n = 786) pediatric patients, which included genotyping whereby a lower intracranial TCD velocity was observed in HbSβ 0 vs HbSS participants, but with no significant impact on infarct prevalence. 4 Certain individuals with intracranial stenosis would be expected to have elevated TCD velocities and as such this prior work is consistent with no patients here with HbSβ 0 having vasculopathy.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…These findings are largely consistent with a prior study of HbSβ 0 (n = 22) and HbSS (n = 786) pediatric patients, which included genotyping whereby a lower intracranial TCD velocity was observed in HbSβ 0 vs HbSS participants, but with no significant impact on infarct prevalence. 4 Certain individuals with intracranial stenosis would be expected to have elevated TCD velocities and as such this prior work is consistent with no patients here with HbSβ 0 having vasculopathy.…”
supporting
confidence: 82%
“…Yet the prevalence of cerebral infarcts was not statistically different for HbSβ 0 (27.8%) vs HbSS (30.8%) individuals. 4 These data collectively suggest that some hematological differences in phenotype may not manifest as tissue injury.…”
mentioning
confidence: 93%
“…power to compare VOP event rate and occurrence between patients with HbSS and those with HbSb 0 -thalassemia, and no difference was observed in a prior study. 40 Therefore, we combined the genotypes for both groups of participants for the current analysis. Most participants (91.4%-81%) had no VOP events across each year of life, whereas 5.2% to 8.8% had 1 VOP event per year.…”
Section: Genetic Modifiers Of Rbc %Hbfmentioning
confidence: 99%
“…The clinical features of HbS + -thal and HbSC are generally less severe than those in SCA [18]. HbS 0 -thal is generally considered clinically indistinguishable from SCA, although some studies have reported a slightly lower incidence of SCD comorbidities [19].…”
Section: Hemoglobin Disordersmentioning
confidence: 99%